Halal Awareness in Online Social Networks. How Consumers Percept Halal Cosmetics in Indonesia and Malaysia - Respati, Titik; Jamilah, Lina; Alamsyah, Indra Fajar; Abdulhadi, Abdulrazak (KnE Social Sciences, 2024)
Cosmetics is one of the products offered to meet consumers’ secondary needs and desires to appear more beautiful and attractive. Worldwide, Muslim consumers are increasingly asserting their sensibilities in the market for cosmetic products. The cosmetics and personal care industry has emerged as one of the most prominent and fastest-growing markets, especially among millennials worldwide. This study explores the factors determining the millennial generation’s choice of halal cosmetics. This study used the exploratory factor analysis (EFA) method with 202 millennial respondents from Indonesia and Malaysia using the purposive sampling method. Data were collected using validated questionnaires in six categories. Of the 400 questionnaires distributed, 224 were returned to the research team and only 202 questionnaires could be used in this study. The results of this study included six main factors that can increase the millennial generation’s interest in making choices about halal cosmetics. They were social media campaigns; influencer trustworthiness; halal awareness; brand curiosity in social media; cosmetics advertisement language; brand trust and product quality. Based on previous studies, this study has a novelty by conducting an exploratory study using the EFA method. Keywords: digital marketing, exploratory factor analysis, halal cosmetics, millennial generation